Differential expression of the two nonallelic proinsulin genes in the developing mouse embryo. - Deltour, L (1993)
In the mouse, insulin is produced from two similar but nonallelic genes that encode proinsulins I and II. We have investigated expression of these two genes during mouse embryonic development, using a PCR to detect the two gene transcripts and immunocytochemistry to visualize the two corresponding proteins. At appearance of the dorsal pancreatic anlage at day 9.5 of gestation, both mRNAs could be detected in the embryos, and both proteins were present together in the same cells of the developing pancreas. At days 9.5 and 10.5, when the ventral anlage appears, there were fewer proinsulin II mRNAs than proinsulin I mRNAs. At day 12.5 this ratio was reversed. Proinsulin II mRNA, but not proinsulin I mRNA, could be detected at day 8.5 in the prepancreatic embryo. Proinsulin II mRNA, but not proinsulin I mRNA, was also found in the heads of embryos at day 9.5 and at all later stages studied. These results indicate that the two proinsulin genes are regulated independently, at least in part. They also suggest that insulin might play a role as a growth factor in the developing mouse brain.